Prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome derived from chromosome 11 - Chih-Ping Chen; Ming Chen; Pu-Tsui Wang; Schu-Rern Chern; Shin-Wen Chen; Shih-Ting Lai; Peih-Shan Wu; Shun-Ping Chang; Chen-Wen Pan; Wayseen Wang (Elsevier, 2017)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of a small supernumerary marker chromosome (sSMC) derived from chromosome 11. Case report: A 37-year-old, gravida 3, para 2, woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XX,+mar[18]/46,XX[4]. The parental karyotypes were normal. Level II ultrasound findings were unremarkable. Array comparative genomic hybridization (aCGH) on the DNA extracted from cultured amniocytes revealed no genomic imbalance. The sSMC was characterized by spectral karyotyping (SKY) using 24-color SKY probes and fluorescence in situ hybridization (FISH) using a whole chromosome paint (wcp) probe and a CEP11 (D11Z1) probe. The result was 47,XX,+mar.ish(11)(SKY+, wcp11+, D11Z1+)[16]/46,XX[4], indicating that the sSMC was derived from chromosome 11. A healthy female baby was delivered at 37 weeks of gestation with no phenotypic abnormalities. The cord blood had a karyotype of 47,XX,+mar[32]/46,XX[8]. Polymorphic DNA marker analysis of the blood excluded uniparental disomy 11. The female infant was normal in growth and psychomotor development during follow-ups at two months of age. Conclusion: aCGH, SKY and FISH are useful in prenatal diagnosis of an sSMC derived from the centromeric region of a non-acrocentric chromosome.